Beginning Programming with c++ for Dummies - Davis, Stephen R (Indiana Wiley publising inc, 2010)
Here's programming made easy (and fun!) with this guide to the popular C++ language So you're dreaming of the exciting life of a programmer? You can make it happen with this
contents : writing aprogram - becoming a functional programmer - data structures - advanced strokes
12
Keywords: computer programming; computer software; programming languages